Darfiq's Cross-Marketing Strategy in Facing Competition - Buana, Miftahal Anjarsabda Wira; ZA, Moh. Ah. Subhan (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
Every business must be able to make itself a winner in a market that is always changing rapidly. One of them is by implementing a marketing strategy. However, in reality, several problems occur in the market, including excess capacity resulting in hyper-competition; Too many chasing customers whose numbers continue to decrease, and most products lack differentiation as a result of which many companies experience a decline in market share, stagnation and even go bankrupt because they cannot compete. Lintas Darfiq, which is an Umrah travel service provider located at Karah Agung Number 1 Surabaya and Ruko Planet Number 5 Jalan Lamongan, has only been running for 4 years, with an increase in the number of pilgrims which is sometimes no more than 25% which is less significant for the management which can be said to be stagnant because management has not yet dared to fight the price, lack of management in finding informants and new markets. For Lintas Darfiq, who is new to the Umrah travel business, the majority of which is oriented towards the Lamongan market because in its marketing it is more oriented towards a well-known mentor in Lamongan, sometimes the value of excellence in worship that it has is crossed out due to a lack of commitment in quality. The Surabaya market is very critical compared to the Lamongan market to be accepted by the Surabaya market. Their products must have good and high quality to eliminate the impression that Lintas Darfiq Lamongan is of lower quality than other Umrah travelers in Surabaya. This research method uses a descriptive qualitative approach. Data collection techniques were carried out through a preliminary survey and field studies consisting of interviews, observation and documentation. The results of the study found that Lintas Darfiq is in the second column in the second row, using the IFAS and EFAS Matrix, respectively, the IFAS score = 2.90 and EFAS = 2.46. IFAS and EFAS scores are then entered into the IE Matrix and then vertical and horizontal lines are drawn, then a meeting point occurs in quadrant V, which is a concentration diversification strategy, and also explained in the SWOT diagram, Lintas Darfiq is in quadrant 3 which means the company faces an opportunity a very large market but on the other hand it faces some external constraints or threats. The focus of this corporate strategy is to minimize internal problems in the company so that it can overcome threats and seize better market opportunities.